Economic crises, capital transfer restrictions and investor protection under modern investment treaties - Kolo, Abba (2008)
The Asian and Russian financial crises in 1998 and the Argentine economic crisis of 2001 and the claims brought against some of the countries (in particular Argentina) by foreign investors have raised many international law questions, amongst which is the power of host states to impose capital controls that are inconsistent with their bilateral and multilateral investment treaty obligations and which adversely affected the rights of foreign investors.